2014
DOI: 10.1007/s11581-014-1288-8
|View full text |Cite
|
Sign up to set email alerts
|

ac conductivity and NSPT model conduction of KAlP2O7 compound

Abstract: The KAlP 2 O 7 compound was prepared by conventional solid-state reaction technique. The structure is confirmed by X-ray powder diffraction. The frequency-dependent electrical properties of the sample were investigated in the temperature range of 528-668 K and in the frequency range of 209 Hz-5 MHz by impedance spectroscopy. The ac conductivity has been fitted and studied using Jonscher's equation, whose exponent s varied with the temperature, showing that the non-overlapping small polaron tunneling (NSPT) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The non-overlapping small polaron tunnelling conduction mechanism, in which the exponent s increases with increasing temperature. 11,25 The correlated barrier hopping (CBH) model, in which s decreases with increasing temperature. 20,26 The overlapping large polaron tunnelling conduction mechanism, in which the exponent s is both temperature and frequency dependent and s decreases with increasing temperature to a minimum value and then increases as the temperature increases further.…”
Section: Investigation Of the Theory Of The Conduction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-overlapping small polaron tunnelling conduction mechanism, in which the exponent s increases with increasing temperature. 11,25 The correlated barrier hopping (CBH) model, in which s decreases with increasing temperature. 20,26 The overlapping large polaron tunnelling conduction mechanism, in which the exponent s is both temperature and frequency dependent and s decreases with increasing temperature to a minimum value and then increases as the temperature increases further.…”
Section: Investigation Of the Theory Of The Conduction Mechanismmentioning
confidence: 99%
“…9,10 We have previously reported the electrical properties of MAlP 2 O 7 (M ¼ K, Ag, Na) compounds. [11][12][13] In the study reported here, we investigated MAlP 2 O 7 , including its electrical and dielectric properties, using impedance spectroscopy to determine the conduction mechanism. MAlP 2 O 7 can be distinguished by its crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research work has been made in these diphosphate compounds like KAlP 2 O 7 , CsAlP 2 O 7 , NaInP 2 O 7 , and this interesting field has been grown due to the important characterization such as optical characterization [10]. Recent works were published during last two years on diphosphate materials such as KAlP 2 O 7 , NaAlP 2 O 7 and AgFeP 2 O 7 [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Above 300 K, the frequency exponent increases with temperature gradually and it is well consistent with the NSPT model. The frequency exponent in this region is described by , The detailed illustration of all parameters is explained in our previous paper . The lattice constant gradually expands with high temperature, and as soon as its value surpasses the polaron radius, it promotes the formation of a small polaron.…”
Section: Resultsmentioning
confidence: 99%